2012
DOI: 10.1200/jop.2011.000335
|View full text |Cite
|
Sign up to set email alerts
|

Consent Timing and Experience: Modifiable Factors That May Influence Interest in Clinical Research

Abstract: Purpose: Low rates of participation in cancer clinical trials have been attributed to patient, institutional, and study characteristics. However, few studies have examined factors related to the consent process. We therefore evaluated the impact of consent timing and experience on markers of patient interest in research. Methods:We performed a retrospective analysis of patients enrolled in a cancer center tissue repository. During enrollment, patients were asked if they were willing to be contacted in the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Practical issues around planning nurses’ working shifts, timing recruitment (Gerber et al . ) and carrying out recruitment separately from medical procedures (Halkoaho et al . ) are some of the factors that impact on ethical recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Practical issues around planning nurses’ working shifts, timing recruitment (Gerber et al . ) and carrying out recruitment separately from medical procedures (Halkoaho et al . ) are some of the factors that impact on ethical recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of study conduct (eg, reporting of protocol violations) may improve during a trial and improved patient consent to participation in noninterventional clinical research was reported in 1 study for more experienced consenters. 17 We tested for, but did not find any evidence for such a learning curve.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 This low rate of enrollment reflects a wide range of factors, including patient trust in the healthcare system and understanding of study protocols; physician attitudes toward patients and communication skills; and experience of clinical research staff. 210 Limited trial availability also hinders enrollment at many centers. 11,12 Yet, even at sites heavily invested in clinical research that maintain diverse clinical trial portfolios and attract motivated populations, only a small minority of patients are enrolled in research studies.…”
Section: Introductionmentioning
confidence: 99%